New and noteworthy bird records from the island of Seram, Maluku - Ekstrom, Jonathan M. M; Isherwood, Isabel (KUKILA, 2000)
A number of interesting bird records were made by a team of ten biologists from Cambridge University (UK), Universitas Pattimura (Ambon, Maluku), and Wetlands International, (Indonesia), during a three month research and conservation project in 1996 in the proposed Cagar Alam (Nature Reserve) of Wae Bula in northeast Seram. This paper documents five species previously unrecorded on the island and provides information concerning several species of interest in terms of distribution or conservation. Seram still holds large tracts of unexplored and unsurveyed forest which are likely to hold important populations of threatened and endemic species; future visitors are encouraged to extend our limited knowledge of the avifauna of this island.